IMPLEMENTASI KEBIJAKAN PEMBINAAN KESADARAN BELA NEGARA PADA MAHASISWA BIDIKMISI UNIVERSITAS PEMBANGUNAN NASIONAL “VETERAN” JAWA TIMUR - Fanani, Mohammad Ifan; Wibawani, Sri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Fostering awareness of state defense or what is commonly called PKBN is the government's effort to create deterrence to strengthen the defense of the Unitary State of the Republic of Indonesia in the face of all opportunities and threats from within and outside the country. The East Java 'Veteran' National Development University implemented PKBN through extracurricular activities through the Student Activity Unit (UKM) so that a policy of fostering state defense awareness was formed for bidikmisi students at the East Java 'Veteran' National Development University. The purpose of this study was to determine the implementation of state defense awareness policies in bidikmisi students at the 'Veteran' National Development University in East Java. This research is a descriptive qualitative research with research focus based on Edward III's policy implementation model, namely communication, resources, disposition and bureaucratic structure. The results showed that the implementation of the policy of fostering awareness of state defense in Bidikmisi students at the National Veterans Development University of East Java could not be carried out optimally.